miR-141-3p alleviates ulcerative colitis by targeting SUGT1 to inhibit colonic epithelial cell pyroptosis - Rong Yan; Xinghua Liang; Juan Hu (Taylor & Francis Group, 2023)
Ulcerative colitis (UC) is a chronic and recurrent inflammatory disease of the colon that result in the destruction and inflammation of the colonic mucosa. Current research has established a strong correlation between pyroptosis of colonic epithelial cells and the onset and progression of UC. In addition, miRNAs have been implicated in the development and progression of UC and pyroptosis. This aimed of this study was to identify specific miRNAs that could inhibit pyroptosis in colon epithelial cells and alleviate UC. Lipopolysaccharide (LPS) was used to induce inflammation in FHC normal colonic epithelial cells to construct an enteritis cell model and downregulated expression levels of miRNAs were detected in inflammatory bowel disease mucosal tissue model. Pyroptosis indicators were detected using Cell Counting Kit-8, flow cytometry, ELISA, qPCR, western blot, and immunofluorescence, and miRNA target genes were predicted by miRDB, TargetScan, pyroptosis pathway from KEGG, and double luciferase assay was used for verification. The effect of miR-141-3p on colitis was observed in the mouse DSS colitis model. The results showed that miR-141-3p was the most significantly downregulated miRNA in LPS-induced FHC cells, and promoted the proliferation of LPS-induced FHC cells and suppressed their apoptosis. In addition, miR-141-3p decreased the expression of pyroptosis-related proteins such as NLRP3, caspase-1, N-GSDMD, and the other proteins, as well as the release of IL-18 and IL-1β inflammatory factors. Conversely, the miR-141-3p inhibitor promoted LPS-induced FHC pyroptosis. Dual luciferase experiments confirmed that miR-141-3p could target the HSP90 molecular chaperone SUGT1. Further experiments demonstrated that SUGT1 overexpression could restore the inhibitory effect of miR-141-3p on pyroptosis, while SUGT1 knockdown could alleviate the promotion of pyroptosis induced by miR-141-3p inhibitor. Furthermore, miR-141-3p alleviated the inflammatory phenotype of mouse colonic mucosa in the mouse DSS colitis model. Therefore, miR-141-3p inhibits LPS-induced pyroptosis of colonic epithelial cells by targeting SUGT1. miR-141-3p could also alleviate DSS-induced colitis in mice, suggesting that miR-141-3p may become a nucleic acid drug for the treatment of UC.